A contribuição da transmídia storytelling no desenvolvimento da leitura proficiente das crianças em processo de alfabetização - Alves, Lúcia de Fátima (2020)
Promoting significant and stimulating learning has become a sine qua non condition for any and all school institutions, at any level and academic modality, in view of the current social conjuncture that requires a holistic formation of the subject to cope with the various situations in collective coexistence. Given this evident prerogative, the formative basis should be the greatest concern of those who embrace the mission of teaching, with literacy being the crucial phase, the foundation from which all other teachings will flow and sustain himself or herself. The literacy process includes reading and writing, which translates into the two ways of communicating in the world. It is at school that this learning takes shape and takes place, or should take place in line with the social expectations and expectations that prevail. It turns out that both reading and writing, which is practiced in the current relationships and social interactions, established in the context of hypermedia, hypertexts and cyberspaces, does not seem to establish connection with what is taught in school institutions, especially in public schools. With regard to reading, this arrhythmia intensifies, because the number of children who leave the literacy cycle without knowing how to read is always higher than those who know. According to the data of the last ANA (2018) on reading proficiency, Brazil reflects a shortfall in the order of 54.73%. What led us to our main question: what procedures and strategies have Brazilian public schools used to develop proficient reading of students in the process of literacy? In this sense, we proceeded our project proposal based on the multiletramentos, from a socio-interactionist perspective, which aimed to develop the proficient reading of the students, in a class of the initial 2nd year of elementary school, of a municipal school located in the municipality of Bayeux. For this, we resort to storytelling (short narratives), of four digital paradidiatic books, using the tool proposed by Narrative Transmedia or Transmedia Storytelling. This tool consists of the art of storytelling using various media, in which each contributes to the sense of the whole. Therefore, in the valley of theoretical references as: the principle proposed by Jenkins (2009), in his studies on the culture of convergence in which, among others, he approaches the way we view communication and media; Marcuschi (2010) contributions in studies on orality and literacy; Gabriel's (2013) proposals on hypermedia and transmedia education; Santaella (2014) and reader training; Soares (2018) theoretical assumptions on literacy; the scientific studies of Dehaene (2012) about reading neurons, among others, which contributed substantially to the development of our proposal. From the application of this study followed many learnings, which went beyond our expectations. The results observed at each stage, contributed and stimulated new effective communicative skills, translated into orality and reading actions. When performing the counting, using the propositions of Transmedia Storytelling, the participating students mobilized knowledge and skills that were once acquired and that were useful in the expansion of the story told. Thus, it was visible the involvement in the direction of a really proficient reading practice. The senses were built and at each construction new senses were emerging, in an unfinished process and continuous imagery potential.